MARTÍNEZ ARIAS, A. (2023). The Master Builder: How the New Science of the Cell is Rewriting the Story of Life. London: Basic Books UK - Redondo García, Antonio (Daimon Revista Internacional de Filosofia, 2026)
Reseña de MARTÍNEZ ARIAS, A. (2023). The Master Builder: How the New Science of the Cell is Rewriting the Story of Life. London: Basic Books UK